High-performance austenitic heat-resistant steel and preparation method thereof
By optimizing chemical composition and process in austenite heat-resistant steel, the γ' phase and carbides are formed, and the problem of insufficient performance of existing austenite heat-resistant steel is solved, and the preparation of high-performance austenite heat-resistant steel is realized. , has excellent high temperature strength and fatigue properties.
Patent Information
- Application Number
- CN202411491254.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-20
AI Technical Summary
The existing austenite heat-resistant steel has low strength, fatigue and creep properties, making it difficult to meet the requirements of use in high temperature environments.
By optimizing chemical composition, adding Ni, Al and Ti elements to form the intermetallic compound γ' phase, combined with carbide and solid solution strengthening, high-performance austenite heat-resistant steel was prepared, using vacuum smelting, electrode annealing, and electroslag weight The melting and aging treatment form steel with excellent high temperature strength, fatigue properties and creep properties.
It significantly improves the tensile strength, yield strength and high-temperature creep properties of austenite heat-resistant steel. The tensile strength at room temperature is ≥1186MPa, the tensile strength at 700℃ is ≥914MPa, and the tensile strength at 800℃ is ≥665MPa, and has Excellent high temperature fatigue performance and durability.
Smart Images

Figure CN119162509A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to new material technology, and in particular to a high-performance austenitic heat-resistant steel and a preparation method thereof. Background Art
[0002] Heat-resistant steel is a type of steel that serves in an environment above 450°C. It has good high-temperature properties, such as high-temperature oxidation resistance, high-temperature strength, good high-temperature creep resistance and durability, etc. It is widely used in the manufacture of high-temperature structural parts for boilers, steam turbines, high-temperature boilers and petrochemical equipment. Heat-resistant steel can be divided into heat-resistant steel, valve steel and oxidation-resistant steel according to its use. Heat-resistant steel has good strength at high temperatures and is mostly used to manufacture load-bearing structural parts at high temperatures, such as boiler superheater and reheater steel P / T91 and P / T92. Valve steel refers to a type of steel specifically used to manufacture intake and exhaust valves for internal combustion engines, such as 4Cr9Si3, 21-4N and 21-4NWNb. Oxidation-resistant steel, also known as oxidation-resistant non-scaling steel, refers to steel with good anti-oxidation effect at high temperatures. Oxidation-resistant steel is mainly used for components in high-temperature environments, such as furnace bottom plates, material racks, furnace tanks, etc., as well as high-temperature furnaces, chemical equipment, oil and natural gas heating equipment, steam generators, heat exchangers, environmental protection equipment and other fields. Representative steel grades include 06Cr25Ni20, 3Cr18Mn12Si2N and 2Cr20Mn9Ni2Si2N.
[0003] Heat-resistant steel can be divided into pearlite steel, martensite steel and austenite steel according to its organization. Pearlite heat-resistant steel is a low-alloy heat-resistant steel with pearlite or bainite as its matrix. There are mainly chromium-molybdenum and chromium-molybdenum-vanadium series. Later, multi-element (such as chromium, tungsten, molybdenum, vanadium, titanium, boron, etc.) composite alloyed steels were developed, and the endurance strength and use temperature of steel gradually increased. However, the total amount of alloying elements is generally about 5% at most, and its organization includes bainite steel in addition to pearlite. Pearlite heat-resistant steel has good high-temperature creep strength and process performance of pearlite heat-resistant steel at 450-620℃, good thermal conductivity, small expansion coefficient, low price, and is widely used in the production of various heat-resistant structural materials in the range of 450-620℃. Such as boiler steel pipes for power stations, turbine impellers, rotors, fasteners, high-pressure vessels for oil refining and chemical industry, waste heat boilers, heating furnace tubes and heat exchanger tubes, etc. Martensitic heat-resistant steel refers to a type of heat-resistant steel that can obtain martensite through heat treatment. It is a type of hardenable heat-resistant steel. The typical grade is Cr13, such as 20Cr13, 30Cr13, 40Cr13, etc. It has a higher hardness after quenching, and different tempering temperatures have different strength and toughness combinations. It is mainly used for steam turbine blades, tableware, and surgical instruments.
[0004] Austenitic heat-resistant steel refers to heat-resistant steel whose structure is austenite at both high and normal temperatures. This type of steel cannot be hardened by heat treatment, and can only use the precipitates in the aging process to strengthen the matrix and obtain certain mechanical properties. This type of steel contains more austenite-forming elements such as nickel, manganese, and nitrogen, and has good high-temperature strength and organizational stability above 600°C. The most typical grade is 1Cr18Ni9, and 0Cr18Ni11Ti, 0Cr18Ni11Nb, Cr17Ni12Mo2, etc. evolved on this basis are used for 600-650°C boiler tubes, etc. In order to improve the carburization resistance and thermal strength of heat-resistant steel, Cr21Ni32AlTi (Incoloy800) has been developed abroad for use in petrochemical and nuclear energy industries. More strengthening elements such as tungsten and molybdenum are added to steels such as Cr14Ni14W2Mo, 0Cr15Ni25Ti2MoAlVB, and 1Cr22Ni20Co20Mo3W3NbN to improve thermal strength. The former is used for exhaust valve materials with high loads, and the latter two grades are used for 700-750℃ high-temperature turbine rotors, bolts, blades, etc. However, the strength and other properties of existing austenitic heat-resistant steels are relatively low, such as tensile strength of 520-700MPa and yield strength of 205-400MPa. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high-performance austenitic heat-resistant steel and a preparation method thereof, so as to solve the problems of low strength, fatigue, durability and creep properties of existing austenitic heat-resistant steel.
[0006] On the one hand, the present invention provides a high-performance austenitic heat-resistant steel, whose chemical composition, measured by weight percentage, includes C: 0.05-0.20%, Si: 0.10-0.30%, Mn: 0.50-1.00%, P: ≤0.015%, S: ≤0.015%, Cr: 17.00-19.00%, Ni: 19.00-24.00%, Al: 1.65-2.65%, Ti: 1.80-3.20%, Nb: 0.50-1.50%, V: 0.1-0.4%, Mo: 0.25-2.50%, and the rest is Fe and unavoidable impurities.
[0007] Furthermore, its chemical composition includes, by weight percentage: C: 0.05-0.10%, Si: 0.20-0.30%, Mn: 0.50-0.80%, P: ≤0.012%, S: ≤0.012%, Cr: 18.00-19.00%, Ni: 22.00-23.00%, Al: 2.00-2.50%, Ti: 2.30-3.00%, Nb: 0.70-1.10%, V: 0.20-0.30%, Mo: 1.00-2.00%, and the rest is Fe and unavoidable impurities.
[0008] Further, its chemical composition, in terms of weight percentage, is C: 0.055%, Si: 0.27%, Mn: 0.85%, P: 0.010%, S: 0.007%, Cr: 17.36%, Ni: 22.05%, Al: 1.85%, Ti: 3.05%, Nb: 0.65%, V: 0.12%, Mo: 0.35%, and the rest is Fe and unavoidable impurities.
[0009] Furthermore, the matrix structure of the austenitic heat-resistant steel is austenite, and the amount of γ' phase in the austenitic heat-resistant steel after solid solution and aging is 10-15%.
[0010] Furthermore, after solution treatment and aging, at room temperature, the tensile strength of the austenitic heat-resistant steel is ≥1186MPa, the yield strength is ≥1030MPa, the elongation after fracture is ≥11.5%, and the cross-sectional shrinkage is ≥18.5%.
[0011] Furthermore, after solution treatment and aging, at 700°C, the tensile strength of the austenitic heat-resistant steel is ≥914MPa, the yield strength is ≥704MPa, the elongation after fracture is ≥14.5%, and the cross-sectional shrinkage is ≥19.5%.
[0012] Furthermore, after solution treatment and aging, at 800°C, the tensile strength of the austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the cross-sectional shrinkage is ≥25%.
[0013] In another aspect, the present invention provides a method for preparing high performance austenitic heat-resistant steel, comprising the following steps:
[0014] S1: Vacuum melting, melting and pouring the raw materials to obtain electrodes;
[0015] S2: electrode annealing, annealing the obtained electrode;
[0016] S3: electroslag remelting, electroslag remelting the annealed electrode to obtain an electroslag ingot;
[0017] S4: After the electroslag ingot is demoulded, it is annealed to obtain austenitic heat-resistant steel.
[0018] Furthermore, the melting rate during remelting is: 4.0-5.0kg / min; the current is controlled at 11000-13000A; the voltage is controlled at 35-45V; after the remelting electrode begins to melt and enters the steady-state stage, the current is controlled at 15000-16000A, and the voltage is controlled at 25-40V; in the later stage of electroslag remelting, the melting rate is gradually reduced to 0.5-1.0kg / min.
[0019] Furthermore, the annealing process of the electroslag ingot is as follows: charge the furnace at 200-300°C, keep warm for 1-2 hours, then heat up to 1130-1150°C at a rate of ≤70°C / h, keep warm for 10-15 hours, then cool down to 750-800°C at a rate of ≤70°C / h and air cool out of the furnace.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. The present invention adds intermetallic compound forming elements Ni, Al and Ti to the steel through reasonable component optimization design to form the intermetallic compound γ' phase Ni3 (Al, Ti), which plays an intermetallic compound strengthening role on the steel; at the same time, carbides also exist in the obtained austenitic steel, which plays a carbide strengthening role; after solid solution and aging treatment, it also plays a solid solution strengthening role. The austenitic heat-resistant steel provided by the present invention can simultaneously contain three types of strengthening: carbide strengthening, intermetallic compound strengthening and solid solution strengthening. Compared with the existing austenitic heat-resistant steel, it has more excellent high-temperature strength, high-temperature fatigue performance, high-temperature endurance and creep performance.
[0022] 2. The present invention rationally designs the chemical composition, and then after vacuum melting, electrode annealing, electroslag remelting, solid solution and aging treatment, the obtained austenitic heat-resistant steel has higher performance. At 700°C, the tensile strength of the austenitic heat-resistant steel is ≥914MPa, the yield strength is ≥704MPa, the elongation after fracture is ≥14.5%, and the cross-sectional shrinkage is ≥19.5%. At 800°C, the tensile strength of the austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the cross-sectional shrinkage is ≥25%.
[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0025] Figure 1 It is the metallographic diagram of Example 2;
[0026] Figure 2 This is the metallographic diagram of Example 5. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0028] Heat-resistant steel is a type of steel specially designed to work at a certain temperature (above 450°C), so heat-resistant steel must have good high-temperature properties, such as resistance to high-temperature oxidation, high-temperature strength, good resistance to high-temperature creep and durability, etc., and its application areas are also relatively wide.
[0029] Heat-resistant steel is divided into pearlite steel, martensitic steel and austenitic steel according to its structure. Pearlite heat-resistant steel is a low-alloy heat-resistant steel with pearlite or bainite structure as its matrix. The steel's long-lasting strength and use temperature are improved by composite alloying with multiple elements (such as chromium, tungsten, molybdenum, vanadium, titanium, boron, etc.). However, the total amount of alloying elements is generally about 5% at most, and it is mainly used in an environment of 450-620℃. Martensitic heat-resistant steel refers to a type of heat-resistant steel that can obtain martensite through heat treatment, and is a type of hardenable heat-resistant steel.
[0030] Austenitic heat-resistant steel refers to heat-resistant steel whose structure is austenite at both high temperature and room temperature. This type of steel cannot be hardened by heat treatment, and can only use the precipitates in the aging process to strengthen the matrix and obtain certain mechanical properties. This type of steel contains more austenite-forming elements such as nickel, manganese, and nitrogen, and has good high-temperature strength and structural stability above 600°C. However, in order to improve the performance of steel, more strengthening elements tungsten and molybdenum are added to the steel to improve the thermal strength. Elements such as Co, W or Mo are also added to the steel to play a solid solution strengthening role to improve its thermal strength. However, the existing austenitic heat-resistant steel has low strength and other properties, and is mainly used in high-temperature environments of 700-750°C.
[0031] The present invention provides austenitic heat-resistant steel with properties such as strength to meet the requirements of use at higher temperatures. Therefore, a high-performance austenitic heat-resistant steel is provided, wherein the chemical composition thereof includes, by weight percentage, C: 0.05-0.20%, Si: 0.10-0.30%, Mn: 0.50-1.00%, P: ≤0.015%, S: ≤0.015%, Cr: 17.00-19.00%, Ni: 19.00-24.00%, Al: 1.65-2.65%, Ti: 1.80-3.20%, Nb: 0.50-1.50%, V: 0.1-0.4%, Mo: 0.25-2.50%, and the remainder is Fe and unavoidable impurities.
[0032] Compared with the prior art, the present invention adds intermetallic compound forming elements Ni, Al and Ti to the steel through reasonable component optimization design to form the intermetallic compound γ' phase Ni3 (Al, Ti), which plays an intermetallic compound strengthening role on the steel; at the same time, carbides also exist in the obtained austenitic steel, which plays a carbide strengthening role; finally, during preparation, it needs to undergo solid solution and aging treatment, which also plays a solid solution strengthening role. The austenitic heat-resistant steel provided by the present invention includes three types of strengthening: carbide strengthening, intermetallic compound strengthening and solid solution strengthening. Compared with the existing austenitic heat-resistant steel, it has more excellent high temperature strength, high temperature fatigue performance, high temperature endurance and creep performance.
[0033] Cr is the main element in valve steel that resists high temperature oxidation and high temperature corrosion, and can improve the thermal strength of steel. When a certain amount of Cr is contained in steel, a dense Cr2O3 film can be formed on the surface of the steel. This film can prevent corrosive gases such as O, S, and N from diffusing into the steel to a certain extent, and can also prevent metal ions from diffusing outward, thereby improving the steel's oxidation resistance and corrosion resistance. However, when the Cr content in the steel is too high, α-Cr phase or σ phase will appear in the structure. These two phases are harmful phases that can deteriorate the performance of the steel. Therefore, the Cr content in the present invention is 17.00-19.00%.
[0034] The anti-oxidation effect of Si element is similar to that of Cr element, but too high Si content will reduce the plasticity and toughness of steel, so the Si content in the present invention is 0.10-0.30%.
[0035] Carbide is a strengthening phase in austenitic steel. Austenitic heat-resistant steel is usually strengthened by carbides, such as M 23 C6, M7C3, MC, M6C, etc. These carbides are precipitated in the steel after solution treatment and aging treatment. Since the precipitated carbides are small in size and dispersed at the grain boundary or between grains, they hinder the movement of dislocations, thereby improving the strength. At the same time, carbides are relatively stable at a certain temperature and are not easy to grow and coarsen, so that the steel exhibits better thermal strength. In the present invention, a certain amount of carbide-forming elements such as Nb, V and Ti are added to the steel to easily form M 23 Carbides such as C6, (Nb,Ti) (C,N) and V (C,N) can effectively prevent grain growth by blocking the movement of grain boundaries at high temperatures. On the other hand, they can prevent dislocations from passing through these particles, thus improving strength.
[0036] Intermetallic compound forming elements Ni, Al and Ti are added to the steel, and these three elements will form the intermetallic compound γ' phase Ni3(Al,Ti). γ' phase is the main strengthening phase in nickel-based heat-resistant alloys and has an L12-type ordered structure. It is a structurally stable phase, and its volume fraction, morphology and size distribution play a vital role in the performance of heat-resistant steel. It plays a key role in improving the room temperature / high temperature mechanical properties, oxidation resistance and corrosion resistance of the alloy. The strengthening mechanism of γ' phase is mainly related to its ordered structure and antiphase domain boundary energy.
[0037] The content of Ni, Al and Ti elements determines the amount of γ′ phase precipitated in the steel. Theoretically, the higher the content of these elements, the more γ′ phase precipitated, and the higher the strength of the steel. However, too much γ′ phase will also lead to a decrease in plasticity and toughness, affecting the use of the steel type, so the appropriate amount of γ′ phase is the key to obtaining ideal comprehensive performance. The present invention found that when the amount of γ′ phase is 10-15%, the heat-resistant steel has good high temperature performance and comprehensive mechanical properties, meeting its use requirements. Therefore, the Ni, Al and Ti in the present invention are Ni: 19.00-24.00%, Al: 1.65-2.65%, Ti: 1.80-3.20% respectively.
[0038] In addition to forming an intermetallic compound strengthening phase, the Ni element also plays a role in regulating the phase. Because the Cr content in the steel is relatively high, Cr is a ferrite-forming element, and Ni is an austenite-forming element. In order to maintain the austenitic state of the steel, a certain amount of Ni needs to be added.
[0039] In order to further increase the strengthening effect of steel, a certain amount of Mo element is also added to the steel. The addition of Mo element mainly plays the role of solid solution strengthening. After the heat-resistant steel is subjected to solid solution treatment, the addition of Mo element with a larger atomic radius will cause lattice distortion, increase the resistance of dislocation movement, and make it difficult to slip, thereby improving the strength and hardness of the heat-resistant steel. However, adding too much Mo element will cause the plasticity of the heat-resistant steel to deteriorate. In the present invention, the Mo content is 0.25-2.50%.
[0040] Specifically, in terms of weight percentage, the chemical composition of austenitic heat-resistant steel includes: C: 0.05-0.10%, Si: 0.20-0.30%, Mn: 0.50-0.80%, P: ≤0.012%, S: ≤0.012%, Cr: 18.00-19.00%, Ni: 22.00-23.00%, Al: 2.00-2.50%, Ti: 2.30-3.00%, Nb: 0.70-1.10%, V: 0.20-0.30%, Mo: 1.00-2.00%, and the rest is Fe and unavoidable impurities.
[0041] Preferably, the chemical composition of the austenitic heat-resistant steel is, in percentage by weight, C: 0.055%, Si: 0.27%, Mn: 0.85%, P: 0.010%, S: 0.007%, Cr: 17.36%, Ni: 22.05%, Al: 1.85%, Ti: 3.05%, Nb: 0.65%, V: 0.12%, Mo: 0.35%, and the rest is Fe and unavoidable impurities.
[0042] Preferably, the chemical composition of the austenitic heat-resistant steel is, in percentage by weight, C: 0.065%, Si: 0.22%, Mn: 0.63%, P: 0.011%, S: 0.007%, Cr: 18.60%, Ni: 21.88%, Al: 2.33%, Ti: 2.78%, Nb: 1.34%, V: 0.33%, Mo: 2.05%, and the rest is Fe and unavoidable impurities.
[0043] The heat-resistant steel of the present invention contains relatively more Ni, Al and Ti elements, which can precipitate the strengthening phase γ' phase during the aging process, which is the most important strengthening phase in the steel. In addition, the present invention also contains a certain amount of Nb and V elements, which can precipitate Nb(C,N) or V(C,N) carbides during the aging process. Such fine dispersed precipitated carbides can hinder the dislocation movement inside the material, thereby improving the material strength. The present invention also contains a certain amount of Mo element, the main function of which is to dissolve into the material matrix and cause lattice distortion. Such lattice distortion hinders the dislocation movement and is also one of the means to improve the material strength.
[0044] Under the multiple strengthening effects, the austenitic heat-resistant steel obtained by the present invention has higher performance. At 800°C, the tensile strength of the austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the cross-sectional shrinkage is ≥25%. At 750°C, 1×10 7 The fatigue limit of the rotating bending test is above 341MPa, and the fatigue limit at 800℃ is above 259MPa.
[0045] The present invention provides a method for preparing high-performance austenitic heat-resistant steel, comprising the following steps:
[0046] S1: Vacuum melting, melting and pouring the raw materials to obtain electrodes;
[0047] S2: electrode annealing, annealing the obtained electrode;
[0048] S3: electroslag remelting, electroslag remelting the annealed electrode to obtain an electroslag ingot;
[0049] S4: After the electroslag ingot is demoulded, it is annealed to obtain austenitic heat-resistant steel.
[0050] Specifically, in step S1, the smelting process is vacuum induction + electroslag remelting, and non-vacuum induction + electroslag remelting, or electric arc furnace + external refining + electroslag remelting can also be used.
[0051] It should be noted that the present invention can adopt various forms of smelting processes to prepare austenitic heat-resistant steel. The present invention adopts a method of combining vacuum induction melting and electroslag remelting.
[0052] In the process of vacuum induction melting, the raw materials are melted into alloy liquid at high temperature, and then the alloy liquid is poured into the mold, and the electrode is demolded after cooling. The raw materials (weight) of vacuum induction smelting are 30-40% of austenitic heat-resistant steel recycled materials, 1-2% of ferrosilicon, 2-4% of ferromanganese, 13-15% of ferrochrome, 1-2% of ferrovanadium, 2-3% of ferroniobium, 1.5-3.5% of sponge titanium, 2-3% of metal aluminum, 0.25-2.50% of metal molybdenum, 15-17% of metal nickel, and 11-20% of pure iron. In addition, during vacuum induction melting, the raw materials are baked before use, and the materials are dense at the bottom and loose at the top, that is, small materials are placed at the bottom and large materials are placed at the top. Nb, Al and Ti are added separately during smelting. The vacuum degree is controlled to be <3.0Pa during smelting. The pouring temperature is 1460℃~1480℃, and the demolding time is 3-4 hours.
[0053] Specifically, in step S2, the electrode annealing process is as follows: load the furnace at 400-600°C, keep it at this temperature for 2-3 hours, then heat it up to 980-1000°C at a rate of ≤100°C / h, keep it at this temperature for 4-5 hours, then cool it down to 700-800°C at a rate of ≤100°C / h, and take it out of the furnace and cool it in the air.
[0054] It should be noted that the alloy liquid is poured into the mold, demolded after cooling, and placed in a heating furnace at 400-600°C. After cooling, the surface of the vacuum smelting electrode is polished and cleaned to remove surface defects, expose the metal surface, and flatten the head; the purpose of annealing is to reduce the internal stress of the steel ingot and avoid cracking.
[0055] Specifically, in step S3, the melting rate during remelting is: 4.0-5.0kg / min; the current is controlled at 11000-13000A; the voltage is controlled at 35-45V; after the remelting electrode begins to melt and enters the steady-state stage, the current is controlled at 15000-16000A, and the voltage is controlled at 25-40V; in the later stage of electroslag remelting, the melting rate is gradually reduced to 0.5-1.0kg / min.
[0056] Specifically, in step S3, the slag composition and components are CaF2 (48±3%), Al2O3 (22±2%), CaO (20±2%), MgO (5.0±0.8%), TiO2 (3.0±0.6%) and SiO2 (≤0.6%).
[0057] It should be noted that before electroslag remelting, the bottom plate in contact with the crystallizer should be cleaned to ensure the flatness of the bottom plate and the absence of ash or dirt on the bottom plate surface. Before using the slag, use a drying furnace to bake at 200-300℃ to remove moisture from the slag.
[0058] Specifically, the annealing process of the electroslag ingot is: charge the furnace at 200-300°C, keep it warm for 1-2 hours, then heat it to 1130-1150°C at a speed of ≤70°C / h, keep it warm for 10-15 hours, then cool it to 750-800°C at a speed of ≤70°C / h and air cool it out of the furnace.
[0059] It should be noted that the present invention reasonably designs the chemical composition, and then after vacuum melting, electrode annealing, electroslag remelting and annealing of electroslag ingots, the obtained austenitic heat-resistant steel has higher performance. The matrix structure of the austenitic heat-resistant steel is austenite, and the amount of γ' phase in the austenitic heat-resistant steel after solid solution and aging is 10-15%.
[0060] Specifically, the solution temperature is 1010-1050°C, the insulation time is 1-2h, and water cooling is performed after insulation.
[0061] Specifically, the aging temperature is 720-760°C, the insulation time is 4-6h, and water cooling is performed after insulation.
[0062] The austenitic heat-resistant steel provided by the present invention includes three types of strengthening: carbide strengthening, intermetallic compound strengthening and solid solution strengthening. Compared with the existing austenitic heat-resistant steel, it has more excellent high-temperature strength, high-temperature fatigue performance, high-temperature durability and creep performance. At room temperature, the tensile strength of austenitic heat-resistant steel is ≥1186MPa, the yield strength is ≥1030MPa, the elongation after fracture is ≥11.5%, and the cross-sectional shrinkage is ≥18.5%. At 700°C, the tensile strength of austenitic heat-resistant steel is ≥914MPa, the yield strength is ≥704MPa, the elongation after fracture is ≥14.5%, and the cross-sectional shrinkage is ≥19.5%. At 750°C, the tensile strength of austenitic heat-resistant steel is ≥814MPa, the yield strength is ≥635MPa, the elongation after fracture is ≥18.0%, and the cross-sectional shrinkage is ≥27.5%. At 800°C, the tensile strength of austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the section shrinkage is ≥25%.
[0063] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.
[0064] Example 1
[0065] The preparation method of high-performance austenitic heat-resistant steel comprises the following steps:
[0066] S1: Vacuum melting, melting and pouring the raw materials to obtain electrodes;
[0067] The raw materials are 30-40% recycled austenitic heat-resistant steel, 1-2% ferrosilicon, 2-4% ferromanganese, 13-15% ferrochrome, 1-2% ferrovanadium, 2-3% ferroniobium, 1.5-3.5% sponge titanium, 2-3% aluminum, 0.25-2.50% molybdenum, 15-17% nickel, and 11-20% pure iron. The raw materials are baked before use, and the materials are dense at the bottom and loose at the top, that is, small materials are placed at the bottom and large materials are placed at the top to prevent "material collapse" during melting.
[0068] Nb, Al and Ti are added separately during smelting to avoid mutual adhesion during melting. The vacuum degree is controlled to be <3.0Pa during smelting. The pouring temperature is 1470±5℃, and the pouring ingot is ф430mm. The demoulding time is 3 to 4 hours. After demoulding, it is immediately sent to the annealing furnace;
[0069] S2: electrode annealing, annealing the obtained electrode;
[0070] The electrode annealing process is: load the furnace at 500℃, keep it at this temperature for 2.5 hours. Heat it up to 990℃ at a rate of 90℃ / h, keep it at this temperature for 4.5 hours. Then cool it down to 750℃ at a rate of 80℃ / h, and take it out of the furnace to cool it in the air.
[0071] S3: electroslag remelting, electroslag remelting the annealed electrode to obtain an electroslag ingot;
[0072] Before using the slag, use a drying furnace to bake it at 200-300℃ to remove moisture from the slag. The slag system composition and composition are CaF2 (48±3%), Al2O3 (22±2%), CaO (20±2%), MgO (5.0±0.8%), TiO2 (3.0±0.6%), and SiO2 (≤0.6%). Welded pseudo electrodes are used. During welding, the electrode and the crystallizer are strictly aligned, and the pseudo electrodes are welded to the non-shrinkage end of the electrode. The zero drift before the electroslag is controlled within ±10kg. The size of the crystallizer is ф508mm (i.e. the size of the electroslag ingot), and argon protection is used during the remelting process.
[0073] The melting rate during remelting is: 4.0-5.0kg / min. The current is controlled at 11000~13000A, and the voltage is controlled at 35~45V. After the remelting electrode begins to melt and enters the steady state stage, the current is controlled at 15000~16000A, and the voltage is controlled at 25~40V. In the later stage of electroslag, the melting rate is gradually reduced to 0.5~1.0kg / min, which is conducive to the shrinkage compensation of electroslag ingots. The electroslag ingot is demoulded after cooling for ≥40 minutes;
[0074] S4: After the electroslag ingot is demoulded, it is annealed to obtain austenitic heat-resistant steel. The electroslag ingot is annealed after demoulding. The annealing process is to charge the furnace at 270°C, keep it warm for 1.5 hours, then heat it to 1140°C at a speed of 60°C / h, keep it warm for 12 hours, and then cool it to 780°C at a speed of 70°C / h and air-cool it out of the furnace.
[0075] The chemical compositions of Examples 1-6 of the present invention and Comparative Example 1 are different, as shown in Table 1, and the preparation methods are shown in Table 2.
[0076] Table 1 Chemical composition of the embodiments of the present invention and the comparative examples (wt%)
[0077]
[0078]
[0079] Table 2 Preparation method
[0080]
[0081] *Comparative Example 1 adopts the preparation method of Example 1.
[0082] Performance Testing
[0083] The above-mentioned Examples 1-6 and Comparative Example 1 were subjected to performance tests, mainly including tensile properties at room temperature and high temperature, rotational bending fatigue limit, endurance life and material creep properties. The test results are shown in Tables 3-9.
[0084] Table 320℃ performance test results
[0085]
[0086] Combined with Examples 1-6 and Comparative Example 1 and referring to Tables 3 and Figure 1-2 It can be seen that the matrix structure of the austenitic heat-resistant steel is austenite, and the amount of γ' phase in the austenitic heat-resistant steel after solid solution and aging is 10-15%. After performance testing, the tensile strength of the austenitic heat-resistant steel is ≥1186MPa, the yield strength is ≥1030MPa, the elongation after fracture is ≥11.5%, and the cross-sectional shrinkage is ≥18.5%.
[0087] Table 4700℃ performance test results
[0088] Group <![CDATA[R m / MPa]]> <![CDATA[R P0.2 / MPa]]> A / % Z / % Example 1 954 754 18.5 26.0 Example 2 940 721 20.5 25.0 Example 3 935 704 17.5 19.5 Example 4 914 781 16.5 24.0 Example 5 1025 803 15.5 22.5 Example 6 1042 828 14.5 23.0 Comparative Example 1 422 245 45.0 32.0
[0089] Table 5750℃ performance test results
[0090]
[0091]
[0092] Table 6800℃ performance test results
[0093] Group <![CDATA[R m / MPa]]> <![CDATA[R P0.2 / MPa]]> A / % Z / % Example 1 681 545 30.5 36.0 Example 2 665 514 34.5 41.5 Example 3 670 523 30.0 40.0 Example 4 707 574 30.5 30.0 Example 5 706 545 30.5 31.0 Example 6 724 556 21.5 25.0 Comparative Example 1 210 116 59.0 65.5
[0094] Combining Examples 1-6 and Comparative Example 1 and referring to Tables 4-6, it can be seen that when the composition design provided by the present invention is adopted, after testing at high temperature, at 700°C, the tensile strength of austenitic heat-resistant steel is ≥914MPa, the yield strength is ≥704MPa, the elongation after fracture is ≥14.5%, and the cross-sectional shrinkage is ≥19.5%. At 750°C, the tensile strength of austenitic heat-resistant steel is ≥814MPa, the yield strength is ≥635MPa, the elongation after fracture is ≥18.0%, and the cross-sectional shrinkage is ≥27.5%. At 800°C, the tensile strength of austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the cross-sectional shrinkage is ≥25%.
[0095] Combining Examples 1-6 and Comparative Example 1 and referring to Tables 1-6, it can be seen that the room temperature and high temperature tensile properties of the embodiments of the present invention are much higher than those of Comparative Example 1. The heat-resistant steel of the present invention contains more Ni, Al and Ti elements, which can precipitate the strengthening phase γ' phase during the aging process. This is the most important strengthening phase in the steel. The amount of γ' phase in the embodiments of the present invention is 10-15%. The amount of γ' phase in Comparative Example 1 is 5.68%.
[0096] In addition, the embodiments of the present invention also contain a certain amount of Nb and V elements, which can precipitate Nb(C, N) or V(C, N) carbides during the aging process. Such fine dispersed precipitated carbides can hinder the movement of dislocations inside the material, thereby improving the strength of the material. The present invention also contains a certain amount of Mo element. The main function of Mo element is to dissolve into the material matrix and cause lattice distortion. This lattice distortion hinders the movement of dislocations and is also one of the means to improve the strength of the material. Under the multiple strengthening effects of the present invention, the performance of the obtained austenitic heat-resistant steel is relatively high.
[0097] Table 7 Rotational bending fatigue properties of the present invention and comparative materials (1×10 7 week)
[0098]
[0099] Combining Examples 1-6 and Comparative Example 1 and referring to Table 7, it can be seen that the embodiments of the present invention and Comparative Example 1 have a temperature of 1×10 7 The fatigue limit of the rotating bending of the steel sheet after 1 week is shown in the table. It can be seen from the table that the fatigue limit of the embodiment of the present invention is significantly higher than that of the comparative example 1, the fatigue limit at 750°C is above 341 MPa, and the fatigue limit at 800°C is above 259 MPa.
[0100] Table 8 Durability of the embodiments of the present invention and the comparative materials (750°C)
[0101]
[0102]
[0103] Combining Examples 1-6 and Comparative Example 1 and referring to Table 8, it can be seen that the fatigue life of the embodiments of the present invention and Comparative Example 1 at 750°C under stresses of 100MPa, 80MPa and 70MPa, it can be seen that the fatigue life of the embodiments of the present invention is significantly higher than that of Comparative Example 1. At 100MPa, the fatigue life of the present invention is more than 312.6h; at 80MPa, the fatigue life of the present invention is more than 604.5h; at 70MPa, the fatigue life of the present invention is more than 1504.4h.
[0104] Table 9 Creep properties of the embodiments of the present invention and comparative materials (750°C)
[0105]
[0106] Combining Examples 1-6 and Comparative Example 1 and referring to Table 9, it can be seen that the creep performance of the embodiments of the present invention and Comparative Example 1 at 750°C under 60MPa, 50MPa and 40MPa stresses is compared. It can be seen from the table that the minimum creep rate of the embodiments of the present invention is significantly lower than that of Comparative Example 1. At 60MPa, the minimum creep rate of the present invention is 3.45×10 -3 % / h or less; at 50MPa, the minimum creep rate of the present invention is 8.69×10 -4 % / h or less; at 40MPa, the minimum creep rate of the present invention is 2.15×10 -5 % / h or less.
[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high performance austenitic heat-resistant steel, characterized in that: Calculated in percentage by weight, its chemical composition includes C: 0.05-0.20%, Si: 0.10-0.30%, Mn: 0.50-1.00%, P: ≤0.015%, S: ≤0.015%, Cr: 17.00-19.00%, Ni: 19.00-24.00%, Al: 1.65-2.65%, Ti: 1.80-3.20%, Nb: 0.50-1.50%, V: 0.1-0.4%, Mo: 0.25-2.50%, and the rest is Fe and unavoidable impurities.
2. The high performance austenitic heat-resistant steel according to claim 1, characterized in that: Calculated in percentage by weight, its chemical composition includes: C: 0.05-0.10%, Si: 0.20-0.30%, Mn: 0.50-0.80%, P: ≤0.012%, S: ≤0.012%, Cr: 18.00-19.00%, Ni: 22.00-23.00%, Al: 2.00-2.50%, Ti: 2.30-3.00%, Nb: 0.70-1.10%, V: 0.20-0.30%, Mo: 1.00-2.00%, and the rest is Fe and unavoidable impurities.
3. The high performance austenitic heat-resistant steel according to claim 1, characterized in that: Calculated in percentage by weight, its chemical composition is C: 0.055%, Si: 0.27%, Mn: 0.85%, P: 0.010%, S: 0.007%, Cr: 17.36%, Ni: 22.05%, Al: 1.85%, Ti: 3.05%, Nb: 0.65%, V: 0.12%, Mo: 0.35%, and the rest is Fe and unavoidable impurities.
4. The high performance austenitic heat-resistant steel according to claim 1 or 2, characterized in that: The matrix structure of the austenitic heat-resistant steel is austenite, and the amount of the γ' phase in the austenitic heat-resistant steel is 10-15% after solid solution and aging.
5. The high performance austenitic heat-resistant steel according to claim 1 or 2, characterized in that: After solution treatment and aging, at room temperature, the tensile strength of austenitic heat-resistant steel is ≥1186MPa, the yield strength is ≥1030MPa, the elongation after fracture is ≥11.5%, and the section shrinkage is ≥18.5%.
6. The high performance austenitic heat-resistant steel according to claim 1 or 2, characterized in that: After solution treatment and aging, at 700°C, the tensile strength of austenitic heat-resistant steel is ≥914MPa, the yield strength is ≥704MPa, the elongation after fracture is ≥14.5%, and the section shrinkage is ≥19.5%.
7. The high performance austenitic heat-resistant steel according to claim 1 or 2, characterized in that: After solution treatment and aging, at 800°C, the tensile strength of austenitic heat-resistant steel is ≥665MPa, the yield strength is ≥514MPa, the elongation after fracture is ≥215%, and the section shrinkage is ≥25%.
8. A method for preparing high performance austenitic heat-resistant steel according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Vacuum melting, melting and pouring the raw materials to obtain electrodes; S2: electrode annealing, annealing the obtained electrode; S3: electroslag remelting, electroslag remelting the annealed electrode to obtain an electroslag ingot; S4: After the electroslag ingot is demoulded, it is annealed to obtain austenitic heat-resistant steel.
9. The method for preparing high performance austenitic heat-resistant steel according to claim 8, characterized in that: The melting rate during remelting is: 4.0-5.0kg / min; the current is controlled at 11000-13000A; the voltage is controlled at 35-45V; after the remelting electrode begins to melt and enters the steady state stage, the current is controlled at 15000-16000A and the voltage is controlled at 25-40V; in the later stage of electroslag remelting, the melting rate is gradually reduced to 0.5-1.0kg / min.
10. The method for preparing high performance austenitic heat-resistant steel according to claim 8, characterized in that: The annealing process of electroslag ingot is as follows: charge the furnace at 200-300℃, keep warm for 1-2 hours, then heat up to 1130-1150℃ at a rate of ≤70℃ / h, keep warm for 10-15 hours, then cool down to 750-800℃ at a rate of ≤70℃ / h and air cool out of the furnace.
